2012
DOI: 10.14214/sf.53
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil carbon and nitrogen transformations to stump removal

Abstract: We studied in central Finland whether stump harvesting after clear felling of coniferous forest poses further short-term changes in soil carbon and nitrogen dynamics when compared to the traditional site preparation method, mounding. Exposed mineral soil patches in Norway spruce (Picea abies) dominated clear-cut stands were sampled 1–5 years after the treatments. The extent of the exposed mineral soil surface was significantly larger at the stump removal sites when compared to the mounding sites. No d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Stump lifting may affect also nutrient transformation processes in the soil e.g. nitrogen mineralization (Kataja-aho et al, 2012). In the case of conventional harvesting, stumps are left in the clear-cut and the nutrients released during the decay of the stumps will be available to the next forest generation (Palviainen et al, 2010).…”
Section: Nutrient Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…Stump lifting may affect also nutrient transformation processes in the soil e.g. nitrogen mineralization (Kataja-aho et al, 2012). In the case of conventional harvesting, stumps are left in the clear-cut and the nutrients released during the decay of the stumps will be available to the next forest generation (Palviainen et al, 2010).…”
Section: Nutrient Removalmentioning
confidence: 99%
“…On the other hand, soil disturbance may induce more intensive mineralization of C and thereby initiate CO 2 emission, which may reduce the stable soil C storage (Grelle et al, 2012). Emission of CO 2 may be higher from stump removal plots compared to mounded plots, which can be attributed to more extensive soil mixing (Kataja-aho et al, 2012). Our results support the assumption that CO 2 emissions from uprooted areas decrease: at the Rõuge study site annual cumulative heterotrophic respiration was lower in the harvested area than in the control plot (1.8 and 2.5 t C ha À1 yr À1 , respectively), indicating reduced CO 2 emission because of the absence of decomposing stump biomass.…”
Section: Carbon Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…methylmercury, from sites due to the ground disturbance as it increases mineralisation (Egnell et al 2007). The documented knowledge about ground disturbance after stump harvesting is however limited, and it has only been studied in relation to the total disturbance on the site, which can vary between 40-70% of the area (Hope 2007;Kataja-aho et al 2012). Soil preparation is mainly performed using separate machines after the stumps have been harvested and forwarded (Kärhä 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the removal of trees would decrease the transpiration from the deep soil, resulting in a relative higher soil moisture that promotes CH 4 production (Castro et al, 2000;Wu et al, 2011). The harvest residue effect on F CH4 was not examined at our site although previous studies indicated that stump removal did not have significant effects on CH 4 flux (Kataja-aho et al, 2012;Sundqvist et al, 2014) and aboveground logging residue had no change on F CH4 (Mäkiranta et al, 2012).…”
Section: Tablementioning
confidence: 96%